The Drosophila bunched gene is a homologue of the growth factor stimulated mammalian TSC-22 sequence and is required during oogenesis. - Dobens, L.L.; Hsu, T.; Twombly, V.; Gelbart, W.M.; Raftery, L.A.; Kafatos, F.C. (Mechanisms of Development, 1997)
A Drosophila melanogaster sequence homologous to the mammalian growth factor-stimulated TSC-22 gene was isolated in an enhancer trap screen for genes expressed in anterodorsal follicle cells during oogenesis. This sequence includes a 225 aa residue open reading frame that encompasses a leucine zipper motif immediately preceded by a highly conserved region (TSC box), similarly located but distinct from the basic domain of bZIP proteins. The gene encoding this sequence, bunched (bun), has been independently isolated and characterized with respect to its role in peripheral nervous system development and eye development (Treisman, J.E., Lai, Z.-C. and Rubin, G.M. (1995) Shortsighted acts in the decapentaplegic pathway in the Drosophila eye development and has homology to a mouse TGF-beta-responsive gene. Development 121, 2835-2845). In agreement with the expression of the enhancer detector insertion, in situ hybridization reveals that bun transcripts localize to the anterior dorsal follicle cells at stages 10-12 of oogenesis. Changes in bun enhancer trap expression in genetic backgrounds that disrupt the grk/Egfr signaling pathway suggest that bun is regulated by growth factor patterning of dorsal anterior follicle cell fates. Clonal analysis shows that bun is required for the proper elaboration of dorsal cell fates leading to the formation of the dorsal appendages.